2021
DOI: 10.1002/anie.202101809
|View full text |Cite
|
Sign up to set email alerts
|

Origins of Endo Selectivity in Diels–Alder Reactions of Cyclic Allene Dienophiles

Abstract: Strained cyclic allenes, first discovered in 1966 by Wittig and co‐workers, have recently emerged as valuable synthetic building blocks. Previous experimental investigations, and computations reported here, demonstrate that the Diels–Alder reactions of furans and pyrroles with 1,2‐cyclohexadiene and oxa‐ and azaheterocyclic analogs proceed with endo selectivity. This endo selectivity gives the adduct with the allylic saturated carbon of the cyclic allene endo to the diene carbons. The selectivity is very gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 50 publications
4
51
0
Order By: Relevance
“…Given the interest in helical MOs as a means to understand related properties and the range of molecular systems in which these MOs appear, it is problematic that the assessment of helical MOs relies on visual inspection alone. It is thus altogether binary; if an MO is shaped like a coil, we may deem it to be helical.…”
Section: Introductionmentioning
confidence: 99%
“…Given the interest in helical MOs as a means to understand related properties and the range of molecular systems in which these MOs appear, it is problematic that the assessment of helical MOs relies on visual inspection alone. It is thus altogether binary; if an MO is shaped like a coil, we may deem it to be helical.…”
Section: Introductionmentioning
confidence: 99%
“…In a collaboration with the Houk group at UCLA, a distortion-interaction analysis demonstrated that interaction energies, related to electron-factors, likely govern regioselectivity . With regard to diastereoselectivity, reactions proceed with endo selectivity with respect to the unreactive cyclic allene double bond. , Given the synthetic utility of this methodology and the ability to understand the regiochemical and stereochemical outcomes, we expect this methodology will see increased usage in chemical synthesis. For example, Schreiber and co-workers have recently harnessed heterocyclic allene chemistry for the synthesis of DNA-encoded libraries …”
Section: Use Of Strained Cyclic Allenes To Access Polycyclic Scaffoldsmentioning
confidence: 99%
“…In this regard, the activation strain model as proposed by Bickelhaupt and co-workers provides an in-depth understanding of the observed chemoselectivity. [19] Thea ctivation energy (DE °)c orresponding to cyclization transition states is bifurcated into distortion energy (DE dist ), which provides an energetic cost of geometric deformation and interaction energy (DE int ), which is responsible for stabilizing electronic interactions between reactants and additives in the transition state.Asshown in Figure 4, DE int is found to be stabilizing in TS FT-GT (cyclization TS of product 4a in the presence of TFE additive, DDE int = À16.3 kcal mol À1 )a sc ompared to that in TS BT-CT (DDE int = 0.0 kcal mol À1 ), presumably due to stronger H-bonding and CÀH•••p interactions (Figure S6). However, steric encumbrance from TFE leads to ag reater degree of geometrical distortion, which is evident from the significantly higher DE dist in TS FT-GT (DDE dist = 18.3 kcal mol À1 )w ith respect to TS BT-CT (DDE dist = 0.0 kcal mol À1 ), signifying that the reaction is selective due to lower extent of ring strain in TS BT-CT than in TS FT-GT .Asimilar trend was observed for the unassisted and HFIP-assisted pathways (Figure 4a nd…”
Section: Angewandte Chemiementioning
confidence: 99%